2010
DOI: 10.1007/s10439-010-0012-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Antagonism Reduces Pain and Modulates Spinal Astrocytic Reactivity After Cervical Nerve Root Compression

Abstract: Relationships between nerve root compression, behavioral sensitivity, spinal cytokines, and glial reactivity are not fully defined for painful cervical nerve root compression. Spinal cytokines were quantified after mechanical root compression (10gf), root exposure to inflammatory chromic gut material (chr), the combination of both insults together (10gf + chr) or sham. TNFalpha and IL-1beta significantly increased at 1 h (p < 0.029). IL-1alpha was significantly increased over normal, sham and chr at 1 h follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 57 publications
(78 reference statements)
1
43
0
1
Order By: Relevance
“…124 135 Comparative effectiveness studies by one group showed similar benefit in pain relief, function, and other outcome measures such as opioid consumption and employment for both steroids and local anesthetic in a variety of cervical diseases including disc hernation. [120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138] Another randomized study in 169 patients with radicular pain found the combination of ESI and conservative treatment consisting of physical therapy and the adjuvants nortriptyline or gabapentin (or both) provided superior relief compared with either treatment alone (mean reduction in pain score of 3.1 in the combination group versus 1.9 in the others at one month; P=0.035). 139 Together, these studies provide limited evidence that ESI is more effective than epidural non-steroid injections but moderate evidence that a series of epidural injections can provide sustained relief.…”
Section: Cervical Discogenic Painmentioning
confidence: 99%
“…124 135 Comparative effectiveness studies by one group showed similar benefit in pain relief, function, and other outcome measures such as opioid consumption and employment for both steroids and local anesthetic in a variety of cervical diseases including disc hernation. [120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138] Another randomized study in 169 patients with radicular pain found the combination of ESI and conservative treatment consisting of physical therapy and the adjuvants nortriptyline or gabapentin (or both) provided superior relief compared with either treatment alone (mean reduction in pain score of 3.1 in the combination group versus 1.9 in the others at one month; P=0.035). 139 Together, these studies provide limited evidence that ESI is more effective than epidural non-steroid injections but moderate evidence that a series of epidural injections can provide sustained relief.…”
Section: Cervical Discogenic Painmentioning
confidence: 99%
“…3 Whiplash is a common cause of chronic neck pain, and the cervical facet joint has been identified as the site of pain in the majority of these cases. 1 Although anesthetic facet joint blocks, application of cytokine antagonists, and corticosteroid injections can provide temporary pain relief for some individuals, 1,9,26 up to 62% of people affected by whiplash injuries report pain lasting 2 years or more after injury. 6 Developing a fundamental understanding of facet joint injuries, and how to treat them following whiplash, has been impeded by the lack of radiographic or magnetic resonance imaging (MRI) evidence of any injury to the structures of the neck in most whiplash patients.…”
Section: Introductionmentioning
confidence: 99%
“…Images were cropped to include a region of interest in the superficial dorsal horn before GFAP or PAR1 expression was quantified using a customized densitometry program created in MATLAB (matrix laboratory), as previously reported. 12,44,47,48 Briefly, spinal cord sections were imaged at 20X magnification, and images were cropped to a uniform region of interest including only the dorsal horn tissue. Cropped images were then inverted, and the percentage of pixels above a pre-defined threshold was measured.…”
Section: Methodsmentioning
confidence: 99%